Combustion and emission characteristics of diesel engine fueled with nanocatalyst and pyrolysis oil produced from the solid plastic waste using screw reactor. (10th October 2021) - Sekar, Manigandan; Praveenkumar, T.R.; Dhinakaran, Veeman; Gunasekar, P.; Pugazhendhi, Arivalagan
Abstract: In recent years, the concerns of non-biodegradable mixed plastic waste have been growing and resulting in strengthening of technologies devoted to convert waste into energy. This study examined the technique to extract plastic oil from mixed plastic, non-biodegradable waste. Further, the mechanical characteristics of plastic pyrolysis oil were done. Pyrolysis method was used to extract the oil from plastic waste with screw reactor and the chemical compounds and the characterization of this oil was analyzed. The Fe2 O3 doped Al2 O3 was dispersed to enhance the quality of Waste pyrolysis oil (PO) by ultrasonication. The performance and emission characteristics of various fuels at different load conditions were analyzed by conducting a series of tests in single cylinder 4 stroke water cooled diesel engine. The benefit of the addition of 25 ppm of Fe2 O3 doped Al2 O3 in PO was represented graphically. A series of tests was conducted for various brake mean effective pressure of 1.3 bar, 2.6 bar, 3.9 bar and 5.2 bar for the test blends, PO (neat pyrolysis oil) and P25A (25% PO+ 75% diesel with 25 ppm of Al2 O3 ). From the procured results, the addition of the novel nanoparticles increases the production of brake power by 35% with reduced emission of 45% and 60% of HC and CO2 respectively. On the other hand, the NOx emission was reduced by 15% and 9 % than the neat plastic oil and diesel fuel. Further, the usage of the pyrolysis oil at 25% generated the positive effects on both combustion and emission compared to neat PO. Highlights: Production of the sustainable energy from the plastic waste has been discussed in detail. Utilization of nanoparticles enhances the emission concentration of pyrolysis-based oil considerably. Combustion and emission characteristics were analyzed. P25A pyrolysis oil blends showed lesser CO2, NOx and HC emissions than neat diesel.